The disclosure of Mental Health Conditions (MHCs) in South African organisations - Houtzamer, Nathalie (Organisational Psychology, 2022)
In recent years, South African organisations have continued to underestimate the far-reaching negative impacts of mental health at work. This can largely be attributed to a lack of understanding and awareness owing to the under-researched nature of mental health conditions (MHCs) in the workplace, within the occupational health psychology (OHP) literature. It has thus become important to understand this phenomenon and raise the awareness needed to combat the negative consequences of MHCs in the workplace. Owing to this need and spurred on by the researcher's experience living with a MHC and her colleague taking his life while battling a MHC in 2016, the researcher sought to investigate the disclosure of MHCs within South African workplaces by affected employees. Specifically, she examined the relationship between when (disclosure timing) disclosure is likely to occur, the people (disclosure targets) to whom disclosure was made, perceived support offered to the people living with MHCs and the disclosers' perceived experiences owing to disclosing a MHC. The target population for the study were employees who have lived with a MHCs within South African workplaces. A sample of (N=109) was used. Data was analysed using the Software Package for Social Sciences (SPSS) and tests such as exploratory factor analysis, descriptive statistics, crosstabulations and the Mann-Whitney U test were used. From the study it was revealed that disclosure of a MHC is more likely to occur after obtaining employment, as opposed to during the selection process. Apart from that it was also discovered that perceived support in respect of employee disclosure of a MHC is significantly lower within the organisation than that from external domains, such as family. In addition, it was found that perceived positive experiences owing to the disclosure of a MHC to an immediate line manager are not significantly different than to the Human Resource Department. Lastly, perceived negative experiences from the disclosure of MHCs to colleagues are not significantly different than disclosure to immediate